AN ANALYSIS OF EXPRESSIVE LANGUAGE DISORDER AND ITS INFLUENCE ON SOCIAL INTERACTION IN EARLY CHILDHOOD (1-6 Years): A PSYCHOLINGUISTIC PERSPECTIVE - Marbun, Rimtahi Bahtra Valentua; Damanik, Bernieke Anggita Ristia (Sindoro: Cendikia Pendidikan, 2025)
Expressive Language Disorder (ELD) is a condition that affects a child's ability to produce language despite having normal cognitive and comprehension skills. This study explores the characteristics of ELD and its relationship with social interaction in early childhood from a psycholinguistic perspective. By examining how language abilities, such as vocabulary usage, sentence construction, and grammatical accuracy, influence social engagement, the study provides insights into the connection between language development and interaction. Through a qualitative approach, the research focuses on identifying patterns in language use and social behaviors among children with ELD. This paper aims to contribute to a understanding of the psycholinguistic aspects of ELD and its relevance to early childhood development, providing a foundation for further study in this field.